MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DIKOMBINASIKAN DENGAN MEDIA ANIMASI PADA MATERI LAJU REAKSI KELAS XI SMA NEGERI 1 PALU - Berlin, I Dewa Gede; Walanda, Daud K.; Ratman, Ratman (Universitas Tadulako, 2013)
Students have difficulties in understanding chemistry subject contained mathematical calculation like on reaction rate topic. Cooperative learning model STAD type can be an alternative for the material contained calculation whereas animation media is for conceptual understanding. The objective of the research was to determine the influence of cooperative learning model STAD type combined with animation media for the eleventh grade students of SMA Negeri 1 Palu in academic year 2012/2013 toward the students’ learning outcome on reaction rate material. This research was quasy experimental using posttest-only control group design. The population was the whole eleventh grade students of science program with the sample determination using purposive sampling method. The sample were class of science program 2 as the experimental class which using cooperative learning model STAD type with animation media whereas class of science program 4 as the control one which using convensional learning method. The research results showed that cooperative learning model STAD type combined with animation media at reaction rate material gave students’ learning outcome higher than convensional method.